Mathematical model of a three-phase-multiphase transformer phases converter with a series connection of coils of each phase of secondary winding - Yu. V. Moskalev (Омский научный вестник)
The article considers a three-phase-multiphase transformer converter of the number of phases with a serial connection of coils of each phase of the secondary winding, its substitution scheme and a linear mathematical model are given. As an example, the analysis of the operation of a manufactured three-phase-seven-phase transformer converter of the number of phases is performed. As a result of electromagnetic tests of the prototype, the parameters of the replacement circuit of the device are determined. Using a mathematical model, the operating characteristics are calculated and constructed. The results of theoretical calculations and experimental measurements are compared. The largest errors obtained when comparing the calculated and experimental values of efficiency and power factor are 3,5 % and 2,2 %, respectively.